Crystalline Sponge Method: X‐ray Structure Analysis of Small Molecules by Post‐Orientation within Porous Crystals—Principle and Proof‐of‐Concept Studies. (3rd August 2021) - Zigon, Nicolas; Duplan, Vincent; Wada, Naoki; Fujita, Makoto
Abstract: This Review discusses, along with the historical background, the principles as well as proof‐of‐concept studies of the crystalline sponge (CS) method, a new single‐crystal X‐ray diffraction (SCXRD) method for the analysis of the structures of small molecules without sample crystallization. The method uses single‐crystalline porous coordination networks (crystalline sponges) that can absorb small guest molecules within their pores. The absorbed guest molecules are ordered in the pores through molecular recognition and become observable by conventional SCXRD analysis. The complex {[(ZnI2 )3 (tpt)2 ]⋅x(solvent)} n (tpt=tris(4‐pyridyl)‐1, 3, 5‐triazine) was first proposed as a crystalline sponge and has been most generally used. Crystalline sponges developed later are also discussed here. The principle of the CS method can be described as "post‐crystallization" of the absorbed guest, whose ordering is templated by the pre‐latticed cavities. The method has been widely applied to synthetic chemistry as well as natural product studies, for which proof‐of‐concept examples will be shown here. Abstract : Crystal growth is not needed for single‐crystal X‐ray structure analysis when the crystalline sponge method is used. This method makes use of single‐crystalline porous coordination networks („crystalline sponges") that can absorb small guest molecules within the pores and make the absorbed guests observable by conventional single‐crystal diffraction. This Review focuses on the principles of this approach as well as proof‐of‐concept studies.